KAJIAN KETERSEDIAAN DAN PENGGUNAAN AIR DARI MATAAIR UNTUK KEBUTUHAN DOMESTIK DI KECAMATAN TURI, KABUPATEN SLEMAN - , MUHAMMAD FIRMAN NUR SAID, Prof. Dr. Sudarmadji, M.Eng.,Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The availability of water on the slopes of Merapi Volcano very abundant especially sourced from springs. However, the eruption that happened in 2006 and 2010 and changes in landuse to the developing area,that affect the condition of the aquifer springs. The location of this research is the District Turi Sleman Regency located on the southern slope of Mount Merapi. The purpose of this study is to study water management, the spatial distribution, water quantity and water quality of the springs that are used by residents of the District Turi, calculate the amount of water needs, especially for domestic needs and analyze the current carrying capacity of the springs to fulfill domestic use of water resident in Districts Turi. The method used is quantitative survey. The data in this study are springs which measured the quality and quantity by purposive sampling, and interviews to the population by random method. The technique of analysis uses descriptive qualitative. There are 21 springs are still used by residents in the District of Turi, 20 springs are perennial springs and 1 springs are intermittent springs. The Springs included in discharge according Meinzer classification is a class V (1-10 liters / sec), class VI (0.1-1 liters / sec), class VII (0.01-0.1 liters / sec), in the dominance of springs class VI and VII, the total discharge is issued for 740,756.85 m3/year. Domestic water needs for drinking, cooking, watering plants and sanitation at this time amounted to 3,388,640.03 m3/year. Water Quality Regulation 20th by Yogyakarta Governor of 2008 belong to class II and IV are influenced by the total of coliform. Carrying capacity of the springs to meet the current needs is not enough. Keywords: springs, water supply, domestic water needs.